DIFFERENT GROWTH MEDIA ON PRODUCTION LEVELS AND NUTRITIONAL CONTENT OF MAGGOT BLACK SOLDIER FLY - Faradila, Soraya; Syamsuddin, Syamsuddin; Muqarramah, Nurfadillah; Jariyah, Ainun; Wahyuni, Sri (Buletin Veteriner Udayana, 2023)
Breeders want relatively cheaper prices, while cheap feed does not guarantee livestock productivity. Development of research based on the use of insects as an alternative source of protein to complement the needs of animal protein is urgently needed. These conditions are harmless to livestock, continuous, nutritious and not in competition with humans. One of the efforts offered is to utilize the maggot Black Soldier Flies (BSF) or Hermetia illucens in processing waste into animal feed which is rich in protein. The purpose of the research was to find out the best media for maggot production levels and nutritional content. This study used a completely randomized design (CRD) with 3 treatments and 5 replications so that there were 15 units. The media used were pumpkin (P1), kapok banana skin (P2) and tembang fish (P3). The results showed that the production values ??for population density, maggot weight and length were 0.80 individuals/cm 3 ; 914.5 g; 14.86 mm and the highest nutrient content (protein: 55.13%) was in tembang fish media (P3). The nutritional content of the maggot maintenance media affects the level of production and the nutritional content of the maggot itself. Media using tembang fish (P3) shows the highest value for maggot production and nutritional content compared to other media. Suggestions for further research are the need for further research using other media to obtain optimal production and nutritional values ??for maggot growth.